Estudo de um conversor CA-CC Boost bridgeless monofásico com CFP e adição de um divisor capacitivo balanceado na saída - Silva Junior, José Cleomon da (2017)
This work presents the study of a single-phase bridgeless Boost converter based on the threestate switching cell (TSSC), with power factor correction (PFC) of the input current and addition of capacitive divider with balanced voltages on the output voltage bus. In this way, it was possible to generate at the output a bus with voltages to feed single-phase inverters with phase-neutral voltage of 127 V, and three-phase inverters with phase-to-phase voltage of 220 V, with the converter connected to the mains voltage of 220 V, since some CA-CC Boost converters topologies with capacitive divider feature may duplify the voltage level at the output, raising the bus voltage level, requiring components that support higher voltage levels. To generate the capacitive divider with balanced voltages at the output of the converter, was inserted the Buck-Boost Balancing Cell (BB-BC) at the output of the Boost converter topology in study. The power factor correction (PFC) of the input current was performed by applying the Average Current Mode Control technique. In BB-BC, the control was done using only one voltage control mesh for the capacitors’ voltage balance. The design and verification of the operation for different types of load are performed via simulation of the topology operating with output power of 1 kW, 220 V input voltage and 400 V total bus voltage.